Using Cross Puzzles to Improve Maharah Kitab on Students at the Al-Ihsan Foundation, Medan - Yushinta Novia Nur Fatikah; Akmal Walad Ahkas (Universitas Pahlawan Tuanku Tambusai, 2022)
This study was structured with the aim of improving students' writing skills using Crossword Puzzle (TTS) media for class VIII students at the Al-Ihsan Foundation, Medan, North Sumatra for the 2021/2022 academic year. This type of research is Classroom Action Research (CAR). This research was conducted in the even semester of the 2021/2022 Academic Year, namely in April-May. The research subjects were students of class VIII of the Al-Ihsan Foundation which consisted of 33 students. The object of research is the students' writing ability. Research data were collected using a test given to each student. Based on the results of the percentage of student learning tests in the first cycle was 76.96% and in the second cycle increased to 88.03%. From the comparison of the two cycles, there was an increase of 11.07%. From the comparison of the two cycles, there is an increase, this means that writing skills (maharah kitabah) using the Crossword Puzzle (TTS) media have increased.